2008
DOI: 10.1016/j.ajhg.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Receptor Pathway Mutations Explain Various Fetal Akinesia Deformation Sequence Disorders

Abstract: Impaired fetal movement causes malformations, summarized as fetal akinesia deformation sequence (FADS), and is triggered by environmental and genetic factors. Acetylcholine receptor (AChR) components are suspects because mutations in the fetally expressed gamma subunit (CHRNG) of AChR were found in two FADS disorders, lethal multiple pterygium syndrome (LMPS) and Escobar syndrome. Other AChR subunits alpha1, beta1, and delta (CHRNA1, CHRNB1, CHRND) as well as receptor-associated protein of the synapse (RAPSN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 42 publications
1
89
0
2
Order By: Relevance
“…If a null mutation resides in the other AChR subunit genes, the affected individual will have no substituting subunit and cannot survive. Indeed, two homozygous missense low expressor or null mutations in CHRNA1 and CHRND caused lethal fetal akinesia (Michalk et al, 2008).…”
Section: Endplate Achr Deficiency Due To Defects In Achr Subunitsmentioning
confidence: 99%
“…If a null mutation resides in the other AChR subunit genes, the affected individual will have no substituting subunit and cannot survive. Indeed, two homozygous missense low expressor or null mutations in CHRNA1 and CHRND caused lethal fetal akinesia (Michalk et al, 2008).…”
Section: Endplate Achr Deficiency Due To Defects In Achr Subunitsmentioning
confidence: 99%
“…The foetal AChR seems to play a pivotal role in neuromuscular organogenesis by acting as a guide for the primary encounter of axon and muscle in utero. [35][36] Escobar syndrome is an antenatal congenital myasthenic disorder in which neuromuscular organogenesis is flawed due to mutation in the γ subunit, encoded by CHRNG gene. Although clinically variable, this syndrome typically presents with arthrogryposis multiplex congenital with joint contractures, pterygia, cryptochism in males and respiratory distress.…”
Section: Escobar Syndromementioning
confidence: 99%
“…However, it has been suggested that mutations within the gamma subunit of the cholinergic receptor nicotinic gamma gene of the acetylcholine receptor (AChR), which has a role in the muscle relaxant effect, is responsible for muscle contractures observed in patients with this disorder (12). Complete or severe functional disruption of fetal AChR causes lethal multiple pterygium syndrome, whereas milder alterations result in fetal hypokinesia with congenital contractures or a myasthenic syndrome later in life (13). The increased frequency of hyperthermia is a condition that must be taken into consideration in determining the anesthetic management (14).…”
Section: Discussionmentioning
confidence: 99%